Efficacy and safety of anlotinib-based treatment in metastatic breast cancer patients - Qian, Yu; Lou, Kexin; Zhou, Hao; Zhang, Lili; Yuan, Yuan (Frontiers in Oncology, 2022)
Objective: To evaluate the efficacy and safety of anlotinib-based treatment in metastatic breast cancer (MBC) patients with failure of standard treatment. Methods: We collected the medical data of 56 female patients with the diagnosis of MBC and had failed the standard treatment before. These patients received at least two cycles of anlotinib-based treatment as the second-line or beyond treatment between October 2019 and April 2022 in Jiangsu Cancer Hospital. The primary endpoint of our study was progression-free survival (PFS), and it was estimated with Kaplan-Meier. The second end points were disease control rate (DCR), objective response rate (ORR), and side effects. Results: The median PFS time of a total of 56 patients was 5.7 months (95% CI, 3.17–8.22months). The ORR and DCR was 28.6% and 71.4%, respectively. In second-line, third-line, and beyond treatment, the median PFS was 11.7 months, 8.7 months, and 4.7 months, respectively. In different subtype of breast cancer, the median PFS was 5.6 months, 5.7months, and 6.4 months in human epidermal growth factor receptor 2 positive (HER2+), hormone receptor positive and HER2 negative (HR+/HER2-), and triple negative breast cancer (TNBC) patients, respectively. Most adverse effects were clinically manageable, and the most common events were platelet count decrease (35.7%), hand-foot syndrome (19.6%), diarrhea (19.6%), and fatigue (17.9%). The most common grade 3 and 4 adverse events were platelet count decrease (25.0%), diarrhea (7.1%), and oral mucositis (5.4%). Conclusion: Anlotinib-based treatment showed good efficacy and manageable toxicity in multi-line treatment of MBC patients who failed the standard treatment.